(untitled) (Revista de Biología Marina y Oceanografía, 2019)
The imperial cormorant (Phalacrocorax atriceps) is one of the most abundant cormorant species in the Chilean channels and fjords. Although its reproductive and non-reproductive distributions have been studied, works on its diet are inexistent. This paper describes the diet and determines the dominance and diversity of the prey consumed during the winter periods of 2011 and 2014 in Caulín Bay, Chiloé, southern Chile. A total of 73 pellets were collected (30 in 2011 and 43 in 2014). Prey were identified and classified into three categories: fishes (53.57%), cephalopods (39.29%) and crustaceans (7.14%). When prey consumption was analyzed according to their distribution in the water column, we observed statistically significant differences in a preference of benthic demersal over pelagic prey.